2023
DOI: 10.1128/msphere.00606-22
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii AP2XII-2 Contributes to Transcriptional Repression for Sexual Commitment

Abstract: Toxoplasma gondii is a parasite that undergoes its sexual stage exclusively in feline intestines, making cats a major source of transmission. A better understanding of the proteins controlling the parasite’s life cycle stage transitions is needed for the development of new therapies aimed at treating toxoplasmosis and the transmission of the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…Pf EELM2 was previously predicted as a Pf MORC interactor (Hillier et al 2019) and identified in a quantitative histone peptide pulldown to be consistently recruited to H2B.Z_K13/14/18a (Hoeijmakers et al 2019). Furthermore, we also detected numerous ApiAP2 transcription factors [ Pf AP2-G5, Pf AP2-O5, Pf AP2-I, PF3D7_1107800, PF3D7_0613800, PF3D7_0420300 and PF3D7_1239200] ( Table 1 ), similar to results reported both by Hillier et al and with Toxoplasma Tg MORC complex (Farhat et al 2020, Antunes et al 2023, Srivastava et al 2023). Pf AP2-G5 (PF3D7_1139300) and Pf AP2-O5 (PF3D7_1449500) were enriched 20.5- and 14.99-fold, respectively, suggesting that these factors are likely major components in-complex with Pf MORC.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Pf EELM2 was previously predicted as a Pf MORC interactor (Hillier et al 2019) and identified in a quantitative histone peptide pulldown to be consistently recruited to H2B.Z_K13/14/18a (Hoeijmakers et al 2019). Furthermore, we also detected numerous ApiAP2 transcription factors [ Pf AP2-G5, Pf AP2-O5, Pf AP2-I, PF3D7_1107800, PF3D7_0613800, PF3D7_0420300 and PF3D7_1239200] ( Table 1 ), similar to results reported both by Hillier et al and with Toxoplasma Tg MORC complex (Farhat et al 2020, Antunes et al 2023, Srivastava et al 2023). Pf AP2-G5 (PF3D7_1139300) and Pf AP2-O5 (PF3D7_1449500) were enriched 20.5- and 14.99-fold, respectively, suggesting that these factors are likely major components in-complex with Pf MORC.…”
Section: Resultssupporting
confidence: 90%
“…Pf MORC association with chromatin remodelers has been shown (Bryant et al 2020), but how Pf MORC regulates gene expression in the asexual stage has not been evaluated. In T. gondii , the Tg MORC: Tg ApiAP2 complex acts as a transcriptional repressor of sexual commitment (Farhat et al 2020, Antunes et al 2023, Srivastava et al 2023). This study found that Pf MORC co-immunoprecipitates with several chromatin remodeling proteins and many ApiAP2 transcription factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of overlapping in vivo binding for AP2-LT and AP2-HC 89 TFs is supported by recent studies that identified AP2-HC complexed with PfHP1 89 at heterochromatic regions, while AP2-LT is a component of the putative PfSAGA transcriptional co-activating complex which is only found in euchromatic regions. While the specific role of PF3D7_0420300 as a TF during P. falciparum asexual blood stage development remains unknown, a previous publication identified its interaction with PfMORC 120 , a putative repressive complex component highly characterized in metazoans [121][122][123][124][125][126][127][128] and recently in Toxoplasma gondii 129,130 . Therefore, we anticipate that a PF3D7_0420300:PfMORC complex would bind genomic regions not bound by AP2-LT or AP2-HC.…”
Section: Discussionmentioning
confidence: 99%